Pengaruh Pembelajaran Sejarah Lokal terhadap Kesadaran Sejarah di SMAN 1 Kecamatan Situjuh Limo Nagari - Yuhardi, Yuhardi (Jurnal Kronologi, 2024)
Interesting history learning is history learning that links learning material with the surrounding environment. The history learning material related to the environment is also referred to as local history material or local history learning. History learning that integrates local history materials into general historical materials allows for a deeper understanding of history itself. In the process of history learning in schools, many teachers have not yet implemented local history learning, resulting in students being more familiar with historical learning from other regions rather than their own. The lack of understanding of local history also impacts students' historical awareness, as historical awareness emerges when students understand their own history. The aim of this research is to determine the effect of local history learning on historical awareness. The local history in this research is Peristiwa Situjuh 15 Januari 1949. This research uses a quasi-experimental method with a population of class XI high school students at SMAN 1 Situjuah Limo Nagari, while the sampling technique used is simple random sampling. The results of the study indicate that 1) there is an effect of local history learning on historical awareness 2) there is a difference in the effect of local history learning and conventional learning models on historical awareness.